NAVIGATING GLOBAL INTEGRATION: THE IMPACT OF TRADE POLICY ON EMERGING MARKETS IN THE GLOBAL SOUTH AND AFRICA - Baah, Richard Grover (PEOPLE: International Journal of Social Sciences, 2024)
This paper explores the impact of trade policy on global economic integration, with a focus on emerging markets in Africa and the Global South. Through a detailed examination of the manufacturing, agriculture, and technology sectors, the study reveals the sector-specific effects of trade policies, highlighting the need for tailored approaches that align with broader development goals. The research underscores the importance of complementary domestic policies and infrastructure, particularly in the context of digital trade, where investment in technology and regulatory frameworks is crucial. The findings suggest that 12while trade policy can drive economic integration, its success depends on the presence of supportive domestic conditions. The study concludes by emphasizing the need for a holistic approach to trade policy that considers the unique challenges and opportunities within each sector.